ARS2 Plays Diverse Roles in DNA Damage Response, Fungal Development, and Pathogenesis in the Plant Pathogenic Fungus Fusarium graminearum - Bui, Duc-Cuong; Kim, Jung-Eun; Shin, Jiyoung; Lim, Jae Yun; Choi, Gyung Ja; Lee, Yin-Won; Seo, Jeong-Ah; Son, Hokyoung (Frontiers in Microbiology, 2019)
Arsenite-resistance protein 2 (Ars2) is an important nuclear protein involved in various RNA metabolisms in animals and plants, but no Ars2 ortholog has been studied in filamentous fungi. Although it is an essential gene in most model eukaryotes, FgARS2-null mutants were viable in the plant pathogenic fungus Fusarium graminearum. The deletion of FgARS2 resulted in pleiotropic defects in various fungal developmental processes. Fgars2 mutants were irregular in nuclear division, and conidial germination was significantly retarded, causing the fungus to manifest its hypersensitive phenotypes under DNA damage stress. While FgARS2 deletion caused abnormal morphologies of ascospores and defective ascospore discharge, our data revealed that FgARS2 was not closely involved in small-noncoding RNA production in F. graminearum. The dominant nuclear localization of FgArs2-GFP proteins and abnormal nuclear division in FgARS2 deletion mutant implicated that FgArs2 functions in the nucleus. Intriguingly, we found that FgArs2 established a robust physical interaction with the cap binding complex (CBC) to form a tertiary complex CBC-Ars2 (CBCA), and disruption of any CBCA complex subunit drastically attenuated the virulence of F. graminearum. The results of the study indicate that Ars2 regulates fungal development, stress response, and pathogenesis via interaction with CBC in F. graminearum and provide a novel insight into understanding of the biological functions of Ars2 in filamentous fungi.